Bonuses and their impact on biased incentive allocations. - Ho, Patricia See Peng. (2008)
The research paper focuses on two variables that could induce bias in reward allocation. Significant results from the study have shown that the size of managers’ and employees’ bonuses does have an impact on whether the manager is biased during reward allocation. In this research paper, the team attempted to delve into the intricacies of performance evaluation and singled out two causes that is believed to contribute to managers’ inclination towards bias during rewards allocation.